2020
DOI: 10.1021/acsapm.0c00348
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multicomponent and Multiblock Copolymers and Their Sustained Release Behavior for Fluorescein Sodium

Abstract: In order to improve the sustained release properties of carriers and explore the effect of copolymer sequence structures on sustained release, 5 groups of 12 block copolymers (12-BCPs) with different sequences were prepared using 4 monomers and the microstructure was controlled by changing the sequence of monomers. The results show that each polymer chain contains an average of 228 monomers and the proportion of 4 monomers basically conforms to 1:1:1:1. The release kinetics of fluorescein sodium (FS) as a drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Fundamental understandings of the relationship between chemical compositions, physical structural arrangements (e.g., block sequence and the length of each block), and hydrophobicity of the copolymers can guide the rational design of their self-assemblies into the desired and controllable morphology. Research has shown that an increase in the number of blocks generally leads to enhanced mechanical properties in the formation of hydrogels. , It is known that the arrangement of blocks affects the secondary structure, water solubility, , and drug release efficiency . It is therefore anticipated that the block sequence can tune the gelation concentration and sol–gel transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental understandings of the relationship between chemical compositions, physical structural arrangements (e.g., block sequence and the length of each block), and hydrophobicity of the copolymers can guide the rational design of their self-assemblies into the desired and controllable morphology. Research has shown that an increase in the number of blocks generally leads to enhanced mechanical properties in the formation of hydrogels. , It is known that the arrangement of blocks affects the secondary structure, water solubility, , and drug release efficiency . It is therefore anticipated that the block sequence can tune the gelation concentration and sol–gel transition.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 25 It is known that the arrangement of blocks affects the secondary structure, 27 water solubility, 27 , 28 and drug release efficiency. 29 It is therefore anticipated that the block sequence can tune the gelation concentration and sol–gel transition. While little research attention is paid to the block arrangement within the polymer chain, this report hopes to provide the missing piece in the puzzle of the self-assembly multiblock polymer structure in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescein sodium contains functional groups such as the carboxyl group, carbonyl group, and phenolic hydroxyl group, which are ubiquitous in various drugs and interact with carriers. Because of this, it is often used as a drug model molecule in the studies of drug carriers [28,29]. Moreover, it was proven that fluorescein sodium is a general substrate of the entire human family of organic anion transporting polypeptides, which are transmembrane proteins that influence the pharmacokinetics and drug-drug interactions of several clinically relevant compounds [30].…”
Section: Introductionmentioning
confidence: 99%